2018
DOI: 10.3390/agronomy8100200
|View full text |Cite
|
Sign up to set email alerts
|

Can Faba Bean Physiological Responses Stem from Contrasting Traffic Management Regimes?

Abstract: Our study examined how faba beans (Vicia faba L.) grown in soil conditions that simulate common traffic management regimes and water availabilities displayed alterations to their physiological state. Physiological changes were tracked through plant and sensor-based measurements, such as evapotranspiration, water use efficiency, aboveground biomass, stomatal conductance, and normalized difference vegetation index. A greenhouse experiment comprised of faba beans were sown into pots of two different soil types th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
(64 reference statements)
2
8
0
Order By: Relevance
“…Our findings also indicate that the outcome of crop NRE at time of harvest could be indicated by the earlier mid‐season NDVI (Figure 2). This is in line with previous reports that related NDVI to winter wheat productivity in southern United States (Raun et al., 2002) and yield potential in canola crops in Manitoba (Holzapfel et al., 2009) enabling the within‐season predictability of crop NUE (Della Chiesa et al., 2019; Guenette & Hernandez‐Ramirez, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings also indicate that the outcome of crop NRE at time of harvest could be indicated by the earlier mid‐season NDVI (Figure 2). This is in line with previous reports that related NDVI to winter wheat productivity in southern United States (Raun et al., 2002) and yield potential in canola crops in Manitoba (Holzapfel et al., 2009) enabling the within‐season predictability of crop NUE (Della Chiesa et al., 2019; Guenette & Hernandez‐Ramirez, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, crop uptake can beneficially compete for this available N (Chai et al., 2020; Van Groenigen et al., 2010). Crop N uptake and potential productivity can be probed during the growing season by conducting measurements of normalized difference vegetation index (NDVI) over crop canopies (Guenette & Hernandez‐Ramirez, 2018; Holzapfel et al., 2009). Della Chiesa, Piñeiro, and Yahdjian (2019) recently reported correlations between canopy NDVI and available soil N. Hence, monitoring NDVI within cropping seasons can potentially provide insights into the temporal patterns of N 2 O fluxes and their mitigation options.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 64 soil pots were prepared. Moist soils were preconditioned in the laboratory room for 1 wk before the experiment (Guenette & Hernandez‐Ramirez, 2018; Lin & Hernandez‐Ramirez, 2020). Soils were maintained at 44% water‐filled pore space (WFPS) (equivalent to 0.264 cm 3 H 2 O cm −3 soil) by daily weighing, adding deionized water, and accounting for plant biomass accumulation over time (Guenette & Hernandez‐Ramirez, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Moist soils were preconditioned in the laboratory room for 1 wk before the experiment (Guenette & Hernandez‐Ramirez, 2018; Lin & Hernandez‐Ramirez, 2020). Soils were maintained at 44% water‐filled pore space (WFPS) (equivalent to 0.264 cm 3 H 2 O cm −3 soil) by daily weighing, adding deionized water, and accounting for plant biomass accumulation over time (Guenette & Hernandez‐Ramirez, 2018). Maintaining 44% WFPS was intended to ensure water availability for optimal plant productivity, and it corresponds to the volumetric soil water content at field capacity (Chai et al., 2020; Kiani et al., 2017): normalWFPS0.33em=GWCBD100fwhere f is the fractional soil porosity (0.60 cm 3 cm −3 ).…”
Section: Methodsmentioning
confidence: 99%
“…They found no significant differences in water use efficiency between the two highest irrigation treatments (100% and 80% ETc). Guenette and Hernandez-Ramirez [12] evaluated the effect of soil compaction in conjunction with irrigation treatments in faba beans and found that maintaining high soil water content helps offset compaction damage. Suarez et al [13] evaluated the combined abiotic stresses of deficit irrigation and saline water on different wine (Cabernet Sauvignon) rootstocks.…”
Section: Et Under Different Cropping Systemsmentioning
confidence: 99%